KUALITAS DAYA PADA INSTALASI LISTRIK DENGAN BEBAN NON LINIER (studi kasus Di Gedung Bengkel Listrik Politeknik Negeri Jakarta ) - Kusnadi Kusnadi; Anicetus Damar Aji (Jurnal Poli-Teknologi, 2016)
ABSTRACTNon linear loads on your electrical installation is the load that uses the equipment of electric machines, power converter as an electric motor or controller loads that use electronic devices such as electronic berballast lamps (Lamps or LED SL). The effect of the use of the load will lead to turunya the quality of the power distribution system, due to the harmonics.This research is intended to analyze power quality parameters in the form of value of THD% in electric Workshop PNJ used as a means of practice students. the many uses of non linear load equipment consisting of the installation of motor-electric motor, and the fluorescents which use electronic ballasts. The entire application the equipment will draw current/voltage of the system in nonsinusoidal and make waves being distorted. Current/Voltage will contain harmonics, which are keseluhan cause the quality of the power system will be bad. The quality of power yag low occurrence ofdisturbances will cause more warming in the equipment, so that the equipment used will be quickly damaged.The results showed the capacitor Bank used in electrical repair shop of 30 KVAR and the results showed THD% average on phasa 22,99%, R = S = 23, 28%, T = 23,59% on time without the capacitor Bank, after using capacitor Banks decline THD% average menjadiR = 5.10%, S = 5.20%, T = 5.18%. From the analysis of the obtained as well, with the capacitor Bank dapatmenaikkanfaktordaya average phasa R = 0.75, S = 0.73, T = 0,71 became phasa R = 0.9, S = 0, 9, T = 0.95.Keywords: Power Quality, Electrical Workshop, Capasitor Bank, THDABSTRAKBeban-beban non linier pada instalasi listrik berasal dari peralatan mesin-mesin listrik, konverter daya dan perangkat elektronik seperti lampu yang berballast elektronik ( Lampu SL atau LED). Efek penggunaan beban akan mengakibatkan turunya kualitas daya pada sistem distribusi., akibat adanya harmonik.Penelitian ini dimaksudkan untuk menganalisis parameter kualitas daya yang berupa nilai dari THD% di Bengkel listrik PNJ yang digunakan sebagai sarana praktek mahasiswa. yang banyak menggunakan peralatan beban non linier yang terdiri dari instalasi motor- motor listrik, dan lampu fluorescent yang menggunakan ballast elektronik. Seluruh aplikasi peralatan tersebut akan menarik arus/tegangan dari sistem secara nonsinusoidal dan membuat gelombang menjadi terdistorsi. Arus/Tegangan akan mengandung komponen harmonik, menyebabkan kualitas daya pada sistem akan menjadi buruk. Kualitas daya yang rendah menimbulkan gangguan terjadinya pemanasan yang lebih pada beban terpasang.Hasil penelitian menunjukkan Kapasitor Bank yang digunakan di bengkel listrik sebesar 30 KVAR dan Hasil penelitian menunjukkan THD% rata-rata pada phasa POLITEKNOLOGI VOL. 15 No. 2 MEI 2016195R=22,99%,S=23, 28%, T=23,59% pada saat tanpa Kapasitor Bank, setelah menggunakan kapasitor Bank terjadi penurunan THD%rata-rata menjadiR=5,10%,S=5,20%, T=5,18%. Dari analisa didapatkan juga, dengan kapasitor Bank dapatmenaikkanfaktordaya rata-rata phasa R= 0,75, S=0,73,T=0,71 menjadi phasa R= 0,9, S=0,9, T=0.95.Kata Kunci: Kualitas daya, Bengkel Listrik, Capasitor Bank, THD.